Comparative Analysis of Complete Chloroplast Genomes of 13 Species in Epilobium, Circaea, and Chamaenerion and Insights Into Phylogenetic Relationships of Onagraceae - Luo, Yike; He, Jian; Lyu, Rudan; Xiao, Jiamin; Li, Wenhe; Yao, Min; Pei, Linying; Cheng, Jin; Li, Jinyu; Xie, Lei (Frontiers in Genetics, 2021)
The evening primrose family, Onagraceae, is a well defined family of the order Myrtales, comprising 22 genera widely distributed from boreal to tropical areas. In this study, we report and characterize the complete chloroplast genome sequences of 13 species in Circaea, Chamaenerion, and Epilobium using a next-generation sequencing method. We also retrieved chloroplast sequences from two other Onagraceae genera to characterize the chloroplast genome of the family. The complete chloroplast genomes of Onagraceae encoded an identical set of 112 genes (with exclusion of duplication), including 78 protein-coding genes, 30 transfer RNAs, and four ribosomal RNAs. The chloroplast genomes are basically conserved in gene arrangement across the family. However, a large segment of inversion was detected in the large single copy (LSC) region of all the samples of Oenothera subsect. Oenothera. Two kinds of inverted repeat (IR) region expansion were found in Oenothera, Chamaenerion, and Epilobium samples. We also compared chloroplast genomes across the Onagraceae samples in some features, including nucleotide content, codon usage, RNA editing sites, and simple sequence repeats (SSRs). Phylogeny was inferred by the chloroplast genome data using maximum-likelihood (ML) and Bayesian inference (BI) methods. The generic relationship of Onagraceae was well resolved by the complete chloroplast genome sequences, showing potential value in inferring phylogeny within the family. Phylogenetic relationship in Oenothera was better resolved than other densely sampled genera, such as Circaea and Epilobium. Chloroplast genomes of Oenothera subsect. Oenothera share a syndrome of characteristics that deviate from primitive pattern of the family, including slightly expanded IR region, intron loss in clpP, and presence of the inversion, which may correlate to the biparental inheritance of the chloroplast.